Insecticidal Effects of Some Essential Oils Against the Confused Flour Beetle (Tribolium confusum du Val) (Col.: Tenebrinoidea) in Stored Wheat - SENER, O.; ARSLAN, M.; DEMIREL, N.; UREMIS, I. (Asian Journal of Chemistry, 2010)
The essential oils obtained from rosemary (Rosmarinus officinalis L.), common thyme (Thymus vulgaris L.), common sage (Salvia officinalis L.) and oregano (Origanum syriacum L.) have been analyzed by GC and GC-MS and tested for their insecticidal properties against the confused flour beetle, Tribolium confusum Du Val (Coleoptera: Tenebrionidae) in stored wheat. The essential oil composition varied with the species. The main constituent of oregano, common thyme, common sage and rosemary oils were γ-terpinene, p-cymene, β-thujone and 1,8-cineole, respectively. Each essential oil was applied at the concentrations of 2, 4, 8, 16 and 32 μL/100 mL jar on the filler paper attached under the surface of the jar cap to determine mortality. Mortality rate of essential oils increased with the increasing concentrations. Of the 4 essential oils screened, 1,8-cineole from rosemary and common sage exhibited the highest activity, followed by β-thujone from common sage and p-cymene from thyme. Therefore, rosemary essential oil could be recommended as a potential source of environment-friendly botanical insecticide in the control of the confused flour beetle.